Efek sitotoksisitas ekstrak etanol 70% curcuma xanthorrhiza roxb. Terhadap sel raw 264.7 yang diinduksi lipopolisakarida "lps" (Laporan Penelitian) - Fika Alifiana; Monica Dewi Ranggaini; Johni Halim (Jurnal Kedokteran Gigi Terpadu, 2022)
Background: Curcuma xanthorrhiza Roxb. has bioactive compounds that are beneficial as anti-inflammatory. To get these compounds need to be extracted. Ethanol 70% can increase the solubility of both polar and non-polar compounds. RAW 264.7 cells with LPS induction cause an inflammatory state due to the active pro-inflammatory cytokines. To suppress the development of inflammation, a cytotoxicity test can be carried out to see the toxic nature of the extract against inflamed cells. Goals: To determine the cytotoxicity effect of 70% ethanol extract of C. xanthorrhiza on LPS-induced RAW 264.7 cells. Methods: In vitro laboratory experimental research. Preparation of extracts of C. xanthorrhiza Roxb. carried out with 70% ethanol then made concentrations of 200, 100, 50, 25, 12.5, 6.25, and 3.125 g/mL. Cytotoxicity was tested using the MTS. Untreated culture medium was used as a negative control and a positive control of diclofenac sodium. Then it was incubated for 24 hours at 37oC. After 24 hours of incubation, MTS was added to the plate and incubated again for 3 hours. The results were read using spectrophotometry. The resulting absorption is equivalent to living cells. The research data were analyzed using one-way ANOVA and Dunnet T3 tests. Results: Extracts of C. xanthorrhiza with concentrations of 200 and 100 g/mL were weakly cytotoxic and at concentrations of 50, 25, 12.5, 6.25, and 3.125 g/mL showed non-toxic effects on LPS-induced RAW 264.7 cells. Based on the IC50, C. xanthorrhiza Roxb. extract had a strong cytotoxic effect on LPS-induced RAW 264.7 cells. Conclusion: C. xanthorrhiza extract was toxic to LPS-induced RAW 264 cells.